Association of metabolic syndrome with various anthropometric and atherogenic parameters in the Kazakh population in China. Issue 1 (December 2016) - Chen, Xiaocui; He, Chunhui; Ma, Yitong; Yang, Yining; Liu, Fen; Ma, Xiang; Li, Xiaomei; Xie, Xiang; Chen, Bangdang
Abstract Background This study aimed to evaluate the association of the metabolic syndrome (MetS) with various anthropometric and atherogenic parameters in adult Kazakh population in China. Methods Four thousand ninety-four Kazakhs were recruited since 2007 to 2010. MetS and its components were confirmed according to IDF criteria. Area under the curve (AUC) of each variable was compared. Sensitivity (Sen), specificity (Spe), shortest distance in receiver's operating characteristic curve (ROC) and cutoff of each variable to diagnose MetS were calculated. Results 28.6 % of men and 31.0 % of women had MetS in the Kazakh population. In men, WHtR had the highest AUC value 0.821, followed by BMI (0.801), TG/HDL-C (0.792), WHR (0.776) and BAI (0.666). In women, WHtR also had the highest AUC value (0.835), following by BMI (0.789), WHR (0.778), TG/HDL-C (0.778) and BAI (0.751). WHtR had the shortest ROC distance that was 0.37 and the optimal cutoff was 0.55 in men. In women, WHtR also had the shortest ROC distance of 0.35 and the optimal cutoff was 0.54. Conclusion WHtR is the best predictor of MetS in both Kazakh men and women according to the IDF criteria.